Desenvolvimento de métodos moleculares para detecção simultânea de fusarium oxysporum f. sp. phaseoli, fusarium solani e curtobacterium flaccumfaciens pv. flaccumfaciens - Oliveira, Maythsulene Inácio de Sousa (2015)
Common bean (Phaseolus vulgaris L.) is grown in Brazil in three different cropping seasons, and in diverse agroecosystems. In such different environments, the crop is exposed to several constraints responsible for yield losses, such as pathogenic organisms. Among common bean relevant diseases, fusarium wilt (Fusarium oxysporum f. sp. phaseoli), dry root-rot (Fusarium solani) and Curtobacterium wilt (Curtobacterium flaccumfaciens pv. flaccumfaciens) have similar symptoms, hindering diagnosis in the field, and whose identification in seed health testing is also limited. In both cases, identification at species level is an important step to manage this root pathogen complex, whose detection can be improved by molecular biology tools. Therefore, this study aimed to: 1) to develop and validate a multiplex PCR (m-PCR) method for simultaneous identification of three common bean pathogens, F. oxysporum f. sp. phaseoli, F. solani and C. flaccumfaciens pv. flaccumfaciens; and 2) develop an isothermal amplification of DNA (LAMP) method to detect of F. oxysporum f. sp. phaseoli on seeds. M-PCR method was developed for identification of isolated colonies, as well as infected seeds. In seeds, total DNA was obtained by alkaline lysis method, which inactivates nucleases during the extraction process. M-PCR allowed the identification of all pathogens, with detection of C. flaccumfaciens pv. flaccumfaciens, F. oxysporum f. sp. phaseoli and F. solani amplicons in agarose gel with respectively 306, 609 and 143 base pairs. Furthermore, m-PCR also reduced costs and time to detect Fusarium oxysporum f. sp. phaseoli from 10 days to three hours. It was not possible to develop an optimized protocol for detection of F. oxysporum f. sp. phaseoli by the LAMP method, using only the tf1 gene for design of primers, since such primers were functional only for amplifying large amounts of target DNA. Based on the negative results with LAMP, it is suggested that further studies should be performed using other DNA sequences available in GenBank database.